HUMAN POTENTIAL IN THE FUNCTION OF INTELLECTUAL CAPITAL CREATION (Heritage, 2020)
The new era in which we find ourselves certainly has many challenges but as well many chances. By entering in, the era of knowledge, we are conditioned to radically change the status of human potential and with that the strategies of relationship towards homo sapiens (reasonable man) as potential. In the knowledge era, man is no longer an extended hand of machines. In order to survive in the game with modern technical-technological development trends, it is inevitable for him to take over its naturally given uncompetitive role of unique thoughtful being with unlimited intellectual potential and inevitable in the process of creating the new value. Constant development, changes conditioned by automation, globalization, informatization, for a "reasonable man" can be an unprecedented threat or a civilizational chance to discover, develop, materialize his hidden intellectual potential. In the conditions of the new economy, intellectual potential takes on not only a leading but a key role. Modern research shows that inventiveness and innovation create a leverage effect, directing the intellectual potential to create new high-tech achievements. There are more and more companies which establish the value of its service or product precisely on the discovery, development, materialization of intellectual potential as an unlimited competitive resource. The subject of this paper is to show the importance of research and finding new approaches, new tools, new methods for detection, development, materialization of unlimited intellectual potential of the "thinking man". The goal of this paper is to raise awareness of the chance, which humanity has not had up until now, in the domain of natural resource from the role of "talking tool" or "extended machine hand" to take on the role of "unique, thinking, creative, inventive, unlimited, potential". In this paper, we also only superficially touched on possible modern methods for discovering, developing, materialization of human potential, such as: business consulting, business coaching, business mentoring.
Keywords: human potential, intellectual capital, intellectual DNA, innovation, business consulting, business coaching, business mentoring